Delivering Universal Health Care to People with Major Limb Loss or Damage in Low and Middle Income Countries - Ackers, Louise. author. aut Link
XX, 229 p. 21 illus., 17 illus. in color.
Keywords: This Open Access book addresses the need for rehabilitation services for people impacted by Major Limb Loss in Low and Middle Income Countries. It focuses on a Complex Intervention study in Uganda supporting the provision of affordable and accessible prosthetic services in a public referral hospital. The book demonstrates the impact that overwhelming dependency on overseas support has had on service development and the delivery of universal health coverage and provides an evidence base to support a change in the contribution that overseas assistance makes to health systems planning. Professor Louise Ackers holds Chair in Global Social Justice in the School of Health and Society at the University of Salford UK and is Chair of Knowledge For Change a UK and Ugandan registered NGO. Professor Jonny Huck holds a Chair in Computational Geography at the University of Manchester. Laurence Kenney is Professor of Rehabilitation Technologies at the University of Salford and Academic Director of the EPSRC Centre for Doctoral Training in Prosthetics and Orthotics. Allan Ndawula is Project Manager for Knowledge For Change and Research Associate in Uganda. Jackson Murungi is an Orthopaedic Technologist and Research Associate with Knowledge For Change, Uganda.